1998
DOI: 10.1128/mcb.18.6.3633
|View full text |Cite
|
Sign up to set email alerts
|

The Position and Length of the Steroid-Dependent Hypersensitive Region in the Mouse Mammary Tumor Virus Long Terminal Repeat Are Invariant despite Multiple Nucleosome B Frames

Abstract: Stimulation of the mouse mammary tumor virus with steroids results in the generation of a DNase I-hypersensitive region (HSR) spanning the hormone responsive element (HRE) in the long terminal repeat. Restriction enzymes were used to characterize the accessibility of various sites within the HSR of mouse mammary tumor virus long terminal repeat-reporter constructions in four different cell lines. The glucocorticoid-dependent HSR was found to span minimally 187 bases, a stretch of DNA longer than that associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 93 publications
10
66
2
Order By: Relevance
“…In 3134 (murine mammary adenocarcinoma) cells, 200 copies of the MMTV-LTR with 800 -1200 GR-binding sites are stably integrated in a head-to-tail orientation near the centromere of chromosome 4. Previous studies have indicated that the hormone response of the MMTV-LTR array as a unit is indistinguishable from that of a single integrated copy of the viral LTR (Fragoso et al, 1998;Kramer et al, 1999;McNally et al, 2000). The array, therefore, provides a good model system to examine the in vivo recruitment of chromatin-remodeling complexes to their target promoter.…”
Section: Brg1 and Brm Chromatin-remodeling Complexes Are Selectively mentioning
confidence: 99%
See 4 more Smart Citations
“…In 3134 (murine mammary adenocarcinoma) cells, 200 copies of the MMTV-LTR with 800 -1200 GR-binding sites are stably integrated in a head-to-tail orientation near the centromere of chromosome 4. Previous studies have indicated that the hormone response of the MMTV-LTR array as a unit is indistinguishable from that of a single integrated copy of the viral LTR (Fragoso et al, 1998;Kramer et al, 1999;McNally et al, 2000). The array, therefore, provides a good model system to examine the in vivo recruitment of chromatin-remodeling complexes to their target promoter.…”
Section: Brg1 and Brm Chromatin-remodeling Complexes Are Selectively mentioning
confidence: 99%
“…GFP-BRM and GFP BRG1 have been previously described (Reyes et al, 1997;de la Serna et al, 2001) and was provided by Christian Muchardt, (Institute Pasteur, Paris, France). The full-length MMTV-LTR driving transcription of the luciferase gene, pRSV-GR (glucocorticoid receptor) and pCMV ␤-Galactosidase (internal control) has been described previously (Lefebvre et al, 1991;Fragoso et al, 1998). All cloned vectors were confirmed by sequencing.…”
Section: Expression Vectorsmentioning
confidence: 99%
See 3 more Smart Citations